FAMILY NERIIDAE - Sepúlveda, Tatiana; de Carvalho, Claudio J. B. (Zootaxa, 2016)
Here we provide a catalog of the Neriidae from Colombia, with all six genera and 17 species in alphabetical order. With each genus we provide references and with each species we include the original name, type-locality, acronym of the institution where the type is deposited and the known geographical distribution. In the case of samples only from Colombia, we provide additional details for locality, relevant synonymy and additional references.